2020
DOI: 10.1021/acs.jpclett.9b03568
|View full text |Cite
|
Sign up to set email alerts
|

Direct Experimental Evidence of Longitudinal and Transverse Mode Hybridization and Anticrossing in Simple Model Fluids

Abstract: A significant number of key properties of condensed matter are determined by the spectra of elementary excitations and, in particular-collective vibrations. However, behaviour and description of collective modes in disordered media (e.g. liquids and glasses) remains a challenging area of modern condensed matter science. Recently, anticrossing between longitudinal and transverse modes was predicted theoretically and observed in molecular dynamics simulations, but this fundamental phenomenon has never been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Experimentally, excitation spectra in fluids can be obtained with inelastic neutron and x-ray scattering [9][10][11][12][13][14][15][16][17]. Yet another approach is to use complex plasmas -the model systems of charged and strongly-interacting particles levitating in a weakly-ionized gas, whose interactions can be tuned, and the motions can be visualized [18][19][20][21]. Molecular dynamics (MD) simulations are also widely used [17,[22][23][24][25][26][27][28][29][30][31][32][33][34] to study collective dynamics in systems with a range of interatomic interactions and, crucially, allow access to a broad range of parameters, including the ones that may not be accessible experimentally.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, excitation spectra in fluids can be obtained with inelastic neutron and x-ray scattering [9][10][11][12][13][14][15][16][17]. Yet another approach is to use complex plasmas -the model systems of charged and strongly-interacting particles levitating in a weakly-ionized gas, whose interactions can be tuned, and the motions can be visualized [18][19][20][21]. Molecular dynamics (MD) simulations are also widely used [17,[22][23][24][25][26][27][28][29][30][31][32][33][34] to study collective dynamics in systems with a range of interatomic interactions and, crucially, allow access to a broad range of parameters, including the ones that may not be accessible experimentally.…”
mentioning
confidence: 99%
“…The value of q-gap (characterizing transverse excitations at small q) has been assumed [30,41,42] to influence the heat capacity of fluids, but this has never been tested directly in either experiments or MD simulations. Another generic phenomenon recently studied with MD simulations, theoretically, and experimentally with the model fluids [21,43] is anticrossing of longitudinal and transverse excitations. It has been demonstrated that structural disorder and ahnarmonicity induce mutual mixing of the modes at large q.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2(a) and 2(d) behave similarly to those reported in Refs. [31,[38][39][40]. In the long-wavelength limit, as usual, these branches are attributed to the longitudinal and transverse collective modes [31,40].…”
Section: Resultsmentioning
confidence: 76%
“…The excitation spectra were obtained using the procedures described in Refs. [31,[37][38][39][40]. First, we calculated the velocity current spectra [31,41]:…”
Section: MD Simulationsmentioning
confidence: 99%